Examining the relationship between socioeconomic status, WASH practices and wasting - Raihan, Mohammad Jyoti; Farzana, Fahmida Dil; Sultana, Sabiha; Haque, Md Ahshanul; Rahman, Ahmed Shafiqur; Waid, Jillian L.; McCormick, Benjamin Joseph James; Choudhury, Nuzhat; Ahmed, Tahmeed J. (© 2017 Public Library of Science, 2018)
This article was published in the PLoS ONE [© 2017 Raihan et al.] and the definitive version is available at: http://doi.org/10.1371/journal.pone.0172134 The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0172134